The presence of microplastics in air environment and their potential impacts on health - Azilan Aini, Sofi; Syafiuddin, Achmad; Bent, Grace-Anne (Universitas Nahdlatul Ulama Surabaya, 2022)
There have been many literature reviews on the presence of MPs in water, but study on the presence of MPs in the air and literature reviews on it have not been done much. study on MPs pollution needs to be collected and summarized into one literature review so that this information is easy to find and not scattered. The results found 16 research articles discussed the findings of MPs in ambient air. The 16 research articles found MPs pollution in each location with different levels, the form of MPs in the air that they found the most was fiber because the fiber was lighter in size compared to other MPs shape like fragment, film, or granule. fiber small surface area and thin shape similar like a thread make it easy to be carried by the wind in the air. it turns out that there are 3 main pathways of how MPs enter the human body. the first is by respiration because MPs have been proven to pollute the air human breath, and this supported by a recent study that found MPs in human lungs, a total of 39 MPs were identified within 11 of the 13 human lung tissue samples. the second way is through consumption, because humans consume a lot of seafood that lives in the sea that is contaminated with MPs. MPs are also found in bottled drinking water, fruit, milk, honey, almost all food and beverages consumed polluted by MPs.